HIGHER EDUCATION STUDENTS’ PERCEPTION TOWARDS THE USE OF CHATBOTS IN WRITING ENGLISH FINAL PAPERS - Ricka Dwi; Daning Hentasmaka (LPPM Universitas PGRI Jombang, 2026)
The rapid advancement of Artificial Intelligence (AI) has increasingly influenced academic writing practices, particularly through the use of chatbots by higher education students in writing final papers. However, concerns remain regarding their impact on students’ creativity, originality, and writing quality. This study investigated the perceptions of 53 higher education students from different universities toward the use of chatbots in writing English final papers. Using a quantitative survey design, data were collected through a questionnaire covering five aspects: clarity, evidence-based writing, structure, cohesion and coherence, and referencing. The findings revealed generally positive perceptions of chatbot use. Students reported that chatbots helped improve clarity by reducing ambiguity and enhancing vocabulary choice. They also supported better organization, logical idea development, and stronger cohesion and coherence through grammar correction and improved argument flow. However, students expressed caution regarding the accuracy and credibility of AI-generated references and evidence-based content. Overall, chatbots were perceived as useful supplementary tools that can enhance academic writing when used responsibly. The study highlights the importance of AI literacy and critical evaluation skills in higher education.